Molecular Profiling of High-Grade B-Cell Non-Hodgkin Lymphomas and Its Clinicopathologic Correlation in an Indian Tertiary Cancer Care Center - Sebastian, Nikhil; P. N, Shoaib Nawaz; Ananthkrishnan, Ramya; Kumanan, J.; Chandran, Chitra; Raja, Thirumalairaj (Indian Journal of Medical and Paediatric Oncology, 2024)
Introduction Double-expressor and double-hit lymphomas (DHL) are known to be more aggressive and have poor outcomes with standard chemotherapy regimens.Objectives To assess the incidence of DHL and triple-hit lymphomas (THL) and correlate them with clinicopathologic parameters.Materials and Methods Patients who were diagnosed with high-grade lymphomas from April 2021 to September 2022 were prospectively followed up, and details comprising clinical and pathological parameters, including the immunohistochemistry expression status and gene rearrangements of MYC, BCL2, and BCL6, were recorded.Results The incidence of DHL and THL in our study was 16.43%. The separate incidence of the DHL-BCL2, DHL-BCL6, and THL groups was 16.43, 13.69, and 2.73%, respectively. The germinal center B cell subtype of histology was predominantly seen in DHLs. MYC, BCL2, and BCL6 expressions do not correlate well with translocations of these genes.Conclusion Double protein expression cannot be used for screening to decide which patients should undergo fluorescence in situ hybridization, as this would result in missing 4.5% of DHLs.
Keywords: double-hit lymphoma; triple-hit lymphoma; double-expressor lymphoma; triple-expressor lymphoma; double protein expression